2021
DOI: 10.1016/j.accpm.2020.10.014
|View full text |Cite
|
Sign up to set email alerts
|

A novel, automated, quantification of abnormal lung parenchyma in patients with COVID-19 infection: Initial description of feasibility and association with clinical outcome

Abstract: Objective Ground-glass opacities are the most frequent radiologic features of COVID-19 patients. We aimed to determine the feasibility of automated lung volume measurements, including ground-glass volumes, on the CT of suspected COVID-19 patients. Our goal was to create an automated and quantitative measure of ground-glass opacities from lung CT images that could be used clinically for diagnosis, triage and research. Design Single centre, retrospective, observational st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Thus, our observation of a reduction in lung volume following COVID-19 is consistent with published studies that have shown persistent lung abnormalities following COVID-19 infection, including reduced forced expiratory volume, vital capacity, and forced vital capacity measured by spirometry [48,49]. Moreover, CT scans showing both reduced lung volume [50] and impaired functional lung volume related to disease severity [51] have been reported. Other studies using pulmonary function tests have reported that lung volumes in patients with mild/moderate COVID-19 are normal [52].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, our observation of a reduction in lung volume following COVID-19 is consistent with published studies that have shown persistent lung abnormalities following COVID-19 infection, including reduced forced expiratory volume, vital capacity, and forced vital capacity measured by spirometry [48,49]. Moreover, CT scans showing both reduced lung volume [50] and impaired functional lung volume related to disease severity [51] have been reported. Other studies using pulmonary function tests have reported that lung volumes in patients with mild/moderate COVID-19 are normal [52].…”
Section: Discussionsupporting
confidence: 92%
“…A further retrospective study assessed the feasibility of an automated quantification process of GGOs (−700-−501 HU), one of the most significant lesions of COVID-19 pneumonia, and normally restricted parenchyma (−900-−701 HU). They affirmed that GGOs could be an objective biomarker for lung injury due to a statistically significant correlation between the measured volumes and a respiratory assessment severity score on 6 categories, from absence of hospitalization and inability to resume normal activity (1) to death (7) [114]. On the other hand, a software-based quantitative CT assessment of the normal lung parenchyma percentage (SQNLP) has proven to accurately predict ICU admission if <81.1% (sensitivity 86.5% and specificity 86.7%).…”
Section: Ai In the Stratification And Definition Of Severity And Complications Of Covid-19 Pneumonia At Chest Ctmentioning
confidence: 93%
“…A French retrospective study focused on the automated quantification of GGOs, included in the range from − 700 to − 501 HU), and normally restricted parenchyma, included in the range from − 900 to − 701 HU. The latter was significantly lower in patients admitted to ICU, and GGOs were considered as a biomarker of pulmonary injury, considering a significant correlation between measured lung volumes and a respiratory assessment severity score (7 degrees: ranging from 1 (absence of hospitalization and inability to resume normal activity) to 7 (death)) [ 79 ].…”
Section: Chest Ct and Artificial Intelligence In Covid-19 Patients For The Prediction Of Icu Admissionmentioning
confidence: 99%